Meningkatkan Kemampuan Mengancing Baju pada Anak Disabilitas Intelektual Melalui Media Dressform - Kiswati, Kiswati; Ardisal, Ardisal; Damri, Damri; Mahdi, Arisul; Zulpiani, Mardhatillah (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the effectiveness of using dressform media in improving the buttoning skills of fifth-grade students with intellectual disabilities. This media provides children with opportunities to practice repeatedly without pressure, thereby enhancing focus, learning motivation, and self-confidence. This study employed an experimental method using a Single Subject Research (SSR) design with an A–B pattern. The research subject was one female student with a moderate intellectual disability. Data were collected through observation, interviews, buttoning skill tests, and documentation studies. The data were analyzed using visual analysis within and between conditions, including trend direction, data stability, level changes, and data overlap. The results showed that the subject’s buttoning ability during the baseline phase was in a very low and stable category. After the intervention using dressform media, the buttoning ability showed a significant improvement with an increasing and stable data trend. In the second baseline phase, the subject’s ability was maintained at a high level without intervention. Therefore, it can be concluded that dressform media is effective in improving buttoning skills in children with intellectual disabilities.